INFLUENCE OF SEX ON STUDENTS’ LANGUAGE LEARNING STRATEGIES: A CRITICAL REVIEW - Niwayan Sukraini (Journal of Research on Language Education, 2021)
Due to the importance of providing learning environment that suits the students’ preference in learning a language, many studies have been conducted on the learning strategies employed by the students. Doro and Habok (2013) investigated the learning strategies of Hungarian young students learning English as a foreign language. The instrument they used was the Strategy Inventory for Language Learning (SILL) for adult. It was statistically found that the instrument was reliable and worked well with the young learners. Another result of the study was that meta-cognitive strategies were the most frequently used while compensation strategies were the least frequently employed by the students. The study also discovered that female students showed higher frequency of learning strategy use. I conducted a similar study on Indonesian young students and tried to compare the result. There will be, however, difference in the instrument to collect the data. After consulting an English teacher who teaches young students, I decided to use the modified SILL for Taiwanese children by Lan (2005). This is due to the consideration that Indonesian students might not be able to fill in the complex questionnaire as in the adult version of SILL.The findings show that Meta-cognitive strategies as the most preferred group of the six strategy categories have exactly the same means of both Doro and Habok’s and my studies i.e. 3.2 and female students appeared to use language learning strategies more frequently that male students.